Factors Influencing Greenfield Industrial Cluster Participation in Malaysia - Ismail, Isshammudin (2007)
This thesis is an exploratory study to investigate what are the issues related to the formation of a greenfield effort to develop an ICT cluster in Malaysia throughout the creation of Multimedia Super Corridor (MSC).